Legal Responsibility - García Amado, Juan Antonio (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The author distinguishes legal from moral responsibilities; subsequently he differentiates criminal and administrative responsibilities from contract and non contract liability. Concerning the last one he explores the differences between naturalist and normative approaches.